ACADEMIC MOTIVATION OF THIRD-YEAR MEDICAL STUDENTS AT HAI PHONG UNIVERSITY OF MEDICINE AND PHARMACY AND SOME RELATED FACTORS. (Vietnam Journal of Community Medicine, 2026)
The objective of this study: is to survey the learning motivation of third-year medical students at Hai Phong University of Medicine and Pharmacy and describe some related factors.Research method: a cross-sectional descriptive study on 522 third-year medical students at Hai Phong University of Medicine and Pharmacy. Students completed a survey using a 7-point Likert scale.Results: 63% of students had good learning motivation, with extrinsic motivation being higher than intrinsic motivation (p
Keywords: academic motivation, intrinsic motivation, extrinsic motivation, medical students.